Association Levels of Development the City of Kerman In Terms of Health and Indicators Using the Numerical Taxonomy - Mehdi Raadabadi; Mohsen Barouni; Reza Goudarzi; Najmeh Baghian; Asma Sabermahani (Journal of Community Health Research, 2015)
Abstract Introduction: knowledge and understanding of the situation is necessary for planning to achieve optimal development that this identifying involves separating study regions to planning areas and evaluation of the separate regions by development indicators and analysis and ranking of each area in terms of having development blessings. This study aims to Stratification of Kerman Province Districts in Terms of Health Indicators with taxonomy models.